Health Outcomes and Attitudes Toward Female Genital Cutting in a Community-Based Sample of West African Immigrant Women from High-Prevalence Countries in New York City. Issue 1 (2nd January 2016) - Chu, Tracy; Akinsulure-Smith, Adeyinka M.
ABSTRACT: Female genital cutting (FGC), a deeply rooted cultural practice with high prevalence rates in many West African countries, is considered by many to represent systematic gender-based violence and human rights violation. Although short- and long-term health consequences of FGC have been examined in studies in Africa, the experiences of women who have immigrated to the Western countries such as the United States have remained largely unexplored. We sought to examine prevalence rates of FGC, as well as differences in demographic characteristics, health outcomes, and knowledge, attitudes, and beliefs among West African immigrants. This study employed audio computer-assisted self-interviewing with a community-based sample of 68 women from Gambia, Guinea, Mali, and Sierra Leone living in New York City. The rate of FGC was 68% overall and varied significantly by country, tribe or ethnicity, and marital status. Women with FGC had a significantly higher number of live births and were more likely to report a history of vaginal pain and decreased sexual arousal, but there were no other significant differences in gynecological and obstetric outcomes, sexual functioning, or psychological outcomes. Participants also had similar rates of opposition to FGC, although women with FGC were less likely to assert human rights as a reason to end the practice. Women reported a high level of surprise and unpreparedness for the FGC procedure, and 22% reported that it was done without their parents' consent. Long-term health consequences of FGC among women who have immigrated remain unclear, although resistance to the practice is overwhelming.